Evaluation of the OnSite (Pf/Pan) rapid diagnostic test for diagnosis of clinical malaria - Mohon Abu Naser; Elahi Rubayet; Podder Milka Patracia; Mohiuddin Khaja; Hossain Mohammad Sharif; Khan Wasif A; Haque Rashidul; Alam Mohammad Shafiul (Malaria Journal, 2012)
Abstract Background Accurate diagnosis of malaria is an essential prerequisite for proper treatment and drug resistance monitoring. Microscopy is considered the gold standard for malaria diagnosis but has limitations. ELISA, PCR, and Real Time PCR are also used to diagnose malaria in reference laboratories, although their application at the field level is currently not feasible. Rapid diagnostic tests (RDTs) however, have been brought into field operation and widely adopted in recent days. This study evaluates OnSite (Pf/Pan) antigen test, a new RDT introduced by CTK Biotech Inc, USA for malaria diagnosis in a reference setting. Methods Blood samples were collected from febrile patients referred for malaria diagnosis by clinicians. Subjects were included in this study from two different Upazila Health Complexes (UHCs) situated in two malaria endemic districts of Bangladesh. Microscopy and nested PCR were considered the gold standard in this study. OnSite (Pf/Pan) RDT was performed on preserved whole blood samples. Results In total, 372 febrile subjects were included in this study. Of these subjects, 229 (61.6%) tested positive for Plasmodium infection detected by microscopy and nested PCR. OnSite (Pf/Pan) RDT was 94.2% sensitive (95% CI, 89.3-97.3) and 99.5% specific (95% CI, 97.4-00.0) for Plasmodium falciparum diagnosis and 97.3% sensitive (95% CI, 90.5-99.7) and 98.7% specific (95% CI, 96.6-99.6) for Plasmodium vivax diagnosis. Sensitivity varied with differential parasite count for both P. falciparum and P. vivax. The highest sensitivity was observed in febrile patients with parasitaemia that ranged from 501–1,000 parasites/μL regardless of the Plasmodium species. Conclusion The new OnSite (Pf/Pan) RDT is both sensitive and specific for symptomatic malaria diagnosis in standard laboratory conditions.